Pengaruh Kepemimpinan Kepala Sekolah dan Profesionalitas Guru Terhadap Inovasi Pendidikan di Sekolah Menengah Pertama Negeri 2 Kismantoro Wonogiri Tahun Pelajaran 2021/2022 - Dwi Narti (Pascasarjana IAIN Ponorogo, 2023)
Educational innovations need to be carried out to balance education with the realities of life that are increasingly advanced and also to improve the quality of education in Indonesia, because the quality of education cannot be realized without educational innovation. If an institution does not innovate, it will be left behind or abandoned by customers. This study aims to: 1) determine the influence of the principal's leadership on educational innovation at the State Junior High School 2 Kismantoro Wonogiri; 2) determine the effect of teacher professionalism on educational innovation at State Junior High School 2 Kismantoro Wonogiri; 3) determine the effect of principal leadership and teacher professionalism on educational innovation at Kismantoro Wonogiri 2 Junior High School. This study uses a quantitative approach and is tested with regression analysis. There are three variables that influence each other in this study, namely the principal's leadership and teacher professionalism as the independent variable and educational innovation as the dependent variable. This study uses a saturated sampling technique, where the sample is 57 students, and uses a questionnaire as an instrument in collecting data for the three variables. Based on the data analysis, it can be concluded that (1) there is a significant influence between the principal's leadership on educational innovation at the State Junior High School 2 Kismantoro Wonogiri by 33.7% and providing excellent service is the most dominant factor (2) there is a significant influence between teacher professionalism on educational innovation at Kismantoro 2 Wonogiri Junior High School is 34.3% (3) there is a jointly significant influence between principal leadership and teacher professionalism on educational innovation at Kismantoro Wonogiri 2 Junior High School by 40,1%.